2014
DOI: 10.1080/08927014.2014.976207
|View full text |Cite
|
Sign up to set email alerts
|

Non-toxic plant metabolites regulateStaphylococcusviability and biofilm formation: a natural therapeutic strategy useful in the treatment and prevention of skin infections

Abstract: In the present study, the efficacy of generally recognised as safe (GRAS) antimicrobial plant metabolites in regulating the growth of Staphylococcus aureus and S. epidermidis was investigated. Thymol, carvacrol and eugenol showed the strongest antibacterial action against these microorganisms, at a subinhibitory concentration (SIC) of ≤ 50 μg ml(-1). Genistein, hydroquinone and resveratrol showed antimicrobial effects but with a wide concentration range (SIC = 50-1,000 μg ml(-1)), while catechin, gallic acid, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 48 publications
2
38
0
1
Order By: Relevance
“…Biofilm accumulation by S. epidermidis was much higher than for S. aureus , in all cases. This agrees with previous observations that S. epidermidis is a more prolific biofilm former than S. aureus (Morán et al ). After 48 h, S. epidermidis developed thick, highly structured biofilm matrices on all surface types, and covered a significant portion of the surface area, especially on the nanosmooth, 50 and 100 nm diameter pore surfaces.…”
Section: Resultssupporting
confidence: 93%
“…Biofilm accumulation by S. epidermidis was much higher than for S. aureus , in all cases. This agrees with previous observations that S. epidermidis is a more prolific biofilm former than S. aureus (Morán et al ). After 48 h, S. epidermidis developed thick, highly structured biofilm matrices on all surface types, and covered a significant portion of the surface area, especially on the nanosmooth, 50 and 100 nm diameter pore surfaces.…”
Section: Resultssupporting
confidence: 93%
“…44 reported that MRSA strains were not inhibited by soy isoflavones, including genistein and daidzein (up to 100 μg/mL), and Morán et al . 45 found no MIC for genistein up to 2 mg/mL against S . aureus CECT 59.…”
Section: Discussionmentioning
confidence: 94%
“…SIC of eugenol (≤50 μg/mL) can significantly inhibit the growth of Staphylococcus aureus and Staphylococcus epidermidis (Morán et al., ). When S. carnosus is treated with eugenol (6 to 8.7 μL/mL) for 0, 3, 4, 6, and 8 hr, the highest antibacterial activity is detected after the addition of eugenol for 3 to 4 hr (Manrique, Gibis, Schmidt, & Weiss, ).…”
Section: The Antibacterial Actions and Mechanisms Of Clove Oil And Eumentioning
confidence: 99%